The Integration of LADM and IndoorGML to Support the Indoor Navigation Based on the User Access Rights (A+BE | Architecture and the Built Environment, 2022)
Indoor navigation applications are actively investigated and developed due to their capacity to provide users with essential information in the modern extensive building complexes. Therefore, many researchers have developed a range of indoor navigation applications, which have focused on aspects such as localization, indoor route computation, and human spatial cognition. Unfortunately, current indoor navigation systems do not consider the user's access rights when it comes to navigating safely and effectively. This thesis delivers several contributions, which are based on international standards, to provide Indoor navigation aware of the user’s access rights. The thesis proposes: 1) a combined model of ISO’s LADM and OGC’s IndoorGML; 2) an enhancement of the UML class diagram of the conceptual model of IndoorGML; 3) a 2D LADM country profile of the Saudi Arabia; 4) a 3D LADM country profile of Saudi Arabia; 5) a conversion of the combined LADM and IndoorGML conceptual model to a technical model; 6) definitions of access rights for users of indoor environments during crisis based on the integrated model of LADM and IndoorGML; 7) a 3D web-based prototype application for indoor navigation making use of user access rights. The developed concepts and implementation have been acknowledged by the standardization organization ISO and OGC and considered for amending IndoorGML and LADM.